Optimization of Drying Kinetics and Stone Milling of Chickpea (Cicer arietinum): An Investigation of Moisture Content and Milling Speed Effects on Mill Operative Parameters, Particle Size Distribution, and Flour Composition - Alessio Cappelli; Mauro Zaninelli; Sirio Cividino; Mattia Fiscella; Enrico Cini; Alessandro Parenti; Piernicola Masella (Applied Sciences, 2023)
Chickpeas are one of the most widely consumed legumes in the world. Nevertheless, the literature is lacking studies on the effect of drying and milling processes on chickpea flour characteristics, thus motivating this work. The first aim of this work is to improve chickpea drying process through an in-depth evaluation of drying kinetics; the second aim is to assess the effects of three different moisture contents (8, 10, and 12%) and three milling speeds (120, 220, and 320 RPM) on operative milling parameters, particle size distribution, and flour composition. Our results highlight that moisture content and stone rotational speed have statistically significant effects on milling operative parameters, flour particle size, and chickpea flour composition. As stone rotational speed increases, flour temperature (∆T), average power, and damaged starch content significantly increases. On the other hand, as moisture content increases, energy consumption and specific milling energy increases, while starch and protein content significantly decrease. The results of this study recommend, for the first time in the literature, optimal values of moisture content and milling speed of chickpea. In conclusion, milling chickpeas with 10% moisture content at 320 RPM (milling speed) seems to be the best compromise between milling operative parameters, particle size, and chickpea flour composition.